EFFICACY OF DIFFERENT FUNGICIDES FOR THE CONTROL OF DOWNY MILDEW OF CUCUMBER - S. U. Chaudhry; J. Iqbal; A. Mustafa (Journal of Animal and Plant Sciences, 2009)
A field experiment was conducted to evaluate the performance of different fungicides against downy mildew on cucumber (Cucumis sativus L.) cultivated in high plastic tunnel at the farm of Ch. Khair Din and Sons, Mandiala Warriach, Gujranwala during Rabi, 2006-2007. Five different fungicides namely Dithane M-45, Copper oxychloride 50 WP, Ridomil Gold 72 WP, Success 72 WP and Alliet 80 WP were used at dose rate 5, 4, 2, 2.5 and 2 g/L-1 of water, respectively. Minimum disease incidence was recorded by spraying Success (9%), Ridomil (9.%) and Alliet (11%) compared with control (78%).Number of fruit per plant, length and yield of fruit was significantly higher in treated plots with Ridomil, Success and Alliet as compared to control and other fungicides.
Keywords: Cucumber; Downy mildew; Fungicide; Plastic tunnel; Yield.